Promosi Melalui Katalog Online Menggunakan Coreldraw untuk Meningkatkan Minat Beli di Coffeeshop Blackjack Slowbar Malang - Faizal Islam Akbar Alam; Tri Istining Wardani (Master Manajemen, 2025)
The writing method used is qualitative by using action research methods. The unit of analysis of this research consisted of 2 design experts, 2 marketing experts, the owner of Blackjack Slowbar Coffeeshop Malang and 15 consumers. Data collection methods used include observation, interviews, questionnaires and documents. The EPIC Model and AIDA Model are used as measurement tools for design effectiveness and buying interest in this research. The results showed that in cycle I, the e-catalogue background theme was not used in sync with other themes and there were also some uninterested images. In the second cycle the e-catalogue is considered to be better than before with the value of the effectiveness of using the EPIC rate in the range of 4.65 which is classified as a very effective scale and the value of the effectiveness of buying interest using the AIDA rate in the range of 91% which is classified as a very effective scale. Based on the research that has been done, the conclusion that can be drawn is that using of the EPIC rate design and buying interest according to the AIDA rate guidelines is very effective. However, through this research, suggestions that can be given by researchers regarding the form of promotion that through online catalogues released on the Instagram and ShopeeFood platforms can help promote Blackjack Slowbar Coffeeshop Malang.